Skrining Farmakognosi Tanaman Etnofarmasi Asal Kabupaten Bulukumba yang Berpotensi sebagai Antikanker (Journal of Tropical Pharmacy and Chemistry, 2025)
The use of traditional medicine has long been known and used by the people of South Sulawesi and recorded since the 15th century in lontara 'pabbura. Bulukumba as one of the areas of south Sulawesi inhabited by ethnic of Kajang and ethnic of Makassar has also been used plants to treat several of diseases including. Screening studies pharmacognostic origin Bulukumba conducted to identify medicinal plants used by the community Bulukumba to treat cancer. The research location is the village of Bahari Bonto Lembanna District Bulukumba, The research location is the village Lembana of Bonto Bahari District Regency of Bulukumba, the surveys plants etnofarmasi through sanro (traditional healers), public figures and society who have knowledge of traditional medicine with purposive sampling method. Pharmacognosy screening includes determination etnofarmasi plants that have been collected, organoleptic examination, morphology, anatomy and identification of chemical constituents using color reagent and precipitation reactions. The results obtained five plants etnofarmasi potential for the treatment of cancer, leaf of landep (Barleria prionitis L.) Family Acanthaceae, gewor (Basella rubra L) Famili Acanhtaceae, pecut kuda (Stachytarpheta jamaicensis) Family Loranthaceae, rumput mutiara (Hedyotis corymbosa L.) family Rubiaceae dan gondola (Commelina benghalensis L.) Family Commelinaceae, with chemical ingredients contain flavonoids, saponins, alkaloids, and tannins. The content of flavonoids and alkaloids in plants has the potential to be used as a cancer treatment.